Environmental factors influence on preweaning swine performance - Ferraz, José Bento Sterman; Duarte, Francisco A. de Moura (Pesquisa Agropecuaria Brasileira, 2014)
Individual weights of 746 pigletts at birth, at 21 days of age and at weaning were analysed by Least Squares method considering year and season of birth, litter order, sex and litter sire at birth, as independent variables. The year and the season of the birth affected significantly the 21 day and weaning weights, and the weights were higher with the increase of years. Highest weights were observed during the low temperature season and lowest weights during the hight temperature season. Litter order affected all the weights and a tendency of increasing the weights with flue increasing of order was observed. Sex had significant influence only on birth weight, when the males were heavier. Females had better gain on weight from birth to weaning probably due to the stress caused by castration in the males. Litter sire affected all the weights, although that influence was lowest as the age increased. Generally the weights decreased with the increasing of litter size.